SIMULASI HARDWARE IN THE LOOP UNTUK TAKE-OFF DAN LANDING OTOMATIS PADA QUADROTOR MENGGUNAKAN PIXHAWK DAN jMAVSim - Prasepvianto Estu Broto; Ihsan Ihsan (JFT : Jurnal Fisika dan Terapannya, 2020)
The use of quadrotors in various applications has made development and research in the field of drones grow rapidly. In the research and development process, a testing phase is needed to determine the flying attitude of the quadrotor. Live testing can be risky if something goes wrong. With Hardware in The Loop Simulation, it can be used as a way to minimize the occurrence of these errors. Hardware in The Loop Simulation is a combination of software and hardware simulation. The jMAVSim simulation software is connected to the Pixhawk autopilot and ground control station. The simulation results that have been obtained make it possible to carry out direct testing on the Pixhawk autopilot. From this study, the results of the quadrotor flying attitude during take-off and landing simulations show that the quadrotor is still in a stable condition with changes in pitch and roll angles of less than 1 degree.